Lower risk of death and cardiovascular events in patients with diabetes initiating glucagon‐like peptide‐1 receptor agonists or sodium‐glucose cotransporter‐2 inhibitors: A real‐world study in two Italian cohorts. Issue 7 (15th March 2021) - Baviera, Marta; Genovese, Stefano; Lepore, Vito; Colacioppo, Pierluca; Robusto, Fabio; Tettamanti, Mauro; D'Ettorre, Antonio; Avanzini, Fausto; Fortino, Ida; Nicolucci, Antonio; Roncaglioni, Maria C.; Giorgino, Francesco
Abstract: Aim: To examine the efficacy and safety of glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) and sodium‐glucose cotransporter‐2 (SGLT2) inhibitors compared with other antihyperglycaemic agents (AHAs) in large and unselected populations of the Lombardy and Apulia regions in Italy. Materials and Methods: An observational cohort study of first‐time users of GLP‐1RAs, SGLT2 inhibitors or other AHAs was conducted from 2010 to 2018. Death and cardiovascular (CV) events were evaluated using conditional Cox models in propensity‐score‐matched populations. Adjusted hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated for each region and in a meta‐analysis for pooled risks. Results: After propensity‐score matching, the Lombardy cohort included 18 716 and 11 683 patients and the Apulia cohort 9772 and 6046 patients for the GLP‐1RA and SGLT2 inhibitor groups, respectively. Use of GLP‐1RAs was associated with lower rates of death (HR 0.61, CI 0.56‐0.65, Lombardy; HR 0.63, CI 0.55‐0.71, Apulia), cerebrovascular disease and ischaemic stroke (HR 0.70, CI 0.63‐0.79; HR 0.72, CI 0.60‐0.87, Lombardy), peripheral vascular disease (HR 0.72, CI 0.64‐0.82, Lombardy; HR 0.80, CI 0.67‐0.98, Apulia), and lower limb complications (HR 0.67, CI 0.56‐0.81, Lombardy; HR 0.69, CI 0.51‐0.93, Apulia). Compared with other AHAs, SGLT2 inhibitor use decreased the risk of death (HR 0.47, CI 0.40‐0.54, Lombardy; HR 0.43, CI 0.32‐0.57, Apulia), cerebrovascular disease (HR 0.75, CI 0.61‐0.91, Lombardy; HR 0.72, CI 0.54‐0.96, Apulia), and heart failure (HR 0.56, CI 0.46‐0.70, Lombardy; HR 0.57, CI 0.42‐0.77, Apulia). In the pooled cohorts, a reduction in heart failure was also observed with GLP‐1RAs (HR 0.89, 95% CI 0.82‐0.97). Serious adverse events were quite low in frequency. Conclusion: Our findings from real‐world practice confirm the favourable effect of GLP‐1RAs and SGLT2 inhibitors on death and CV outcomes across both regions consistently. Thus, these drug classes should be preferentially considered in a broad type 2 diabetes population beyond those with CV disease.